Menakar Kebijakan Pendampingan Self Declare Halal oleh Perguruan Tinggi (Studi Kasus di Universitas Nahdlatul Ulama Sidoarjo dan Uin Maulana Malik Ibrahim Malang) - Junaidy, Abdul Basith; Ilmiyah, Zainatul (Universitas Batanghari Jambi, 2024)
This study examines various government efforts to encourage halal product assurance, especially through the creation of derivative regulations and the establishment of the Halal Product Assurance Organizing Agency (BPJPH). However, small to micro-scale business actors still need help, especially related to registration fees and understanding the importance of halal certification. The study aims to explain the role of universities in East Java in assisting halal certification for Micro and Small Enterprises (MSEs) while analyzing the legal aspects and maqashid sharia. Using field research methods and qualitative approaches, it was found that the role of universities is as PPH assistants for MSEs who meet the halal certification criteria through the self-declare route. The implementation of self-declare halal assistance is faced with the obstacle of maintaining the activeness of registered PPH assistants, and there are still business actors who need to meet the requirements in the assistance process, such as lack of information on materials and expired material certification. An effective monitoring system is required to overcome potential errors in the halal certification process. Universities are also expected to be able to create program innovations to strengthen and activate the role of PPH assistants. The government, in this case, especially BPJPH, also needs to create a more consistent policy regarding halal certification registration through the application so that the criteria of the Halal Product Assurance System (SJPH), which is built on five basic principle frameworks (arkanul halal) can be met.